2007
DOI: 10.1007/s10661-007-9661-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) and phenolic endocrine disrupting chemicals in South and Southeast Asian mussels

Abstract: A comprehensive monitoring survey for polycyclic aromatic hydrocarbons (PAHs) and phenolic endocrine disrupting chemicals (EDCs) utilizing mussels as sentinel organisms was conducted in South and Southeast Asia as a part of the Asian Mussel Watch project. Green mussel (Perna viridis) samples collected from a total of 48 locations in India, Indonesia, Singapore, Malaysia, Thailand, Cambodia, Vietnam, and the Philippines during 1994-1999 were analyzed for PAHs, EDCs including nonylphenol (NP), octylphenol (OP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 53 publications
4
56
2
2
Order By: Relevance
“…Consequently, living tissues were more enriched with LMW PAHs in relation to their environments. The present finding agreed with the results of Isobe et al [18], who found LMW/HMW ratios >1.0 in many Asian countries. Skarpheðinsdottir et al…”
Section: Resultssupporting
confidence: 94%
“…Consequently, living tissues were more enriched with LMW PAHs in relation to their environments. The present finding agreed with the results of Isobe et al [18], who found LMW/HMW ratios >1.0 in many Asian countries. Skarpheðinsdottir et al…”
Section: Resultssupporting
confidence: 94%
“…Concentrations of PAHs in Jakarta Bay sediments in this study were the highest so far reported from Asian coastal regions (Takada et al, 1992;Isobe et al, 2004). In the present study, PAH concentrations in mussels were much higher than those reported earlier from the same location or from other South East Asian bays (Tsutsumi et al, 2002, Isobe et al, 2007.…”
Section: Persistent Organic Pollutants (Pops)contrasting
confidence: 68%
“…Isobe et al (2007) reported higher OP values in the mussels from different Asiatic countries (up to 54.4 g/kg d.w. in Tokyo Bay) than those found in this study (<LOD-12.5 g/kg d.w. in mussels).…”
Section: Alkylphenols Results In Mussels and Clamsmentioning
confidence: 93%
“…Li et al (2008) reported NP values in mussels from the Massan Bay (Korea) up to 290 g/kg d.w., which are lower than the maximum value found in this study (120 g/kg w.w. which would be 600 g/kg d.w. considering the measured water content) but similar to the average pollution level found along the Mediterranean coast studied (200 g/kg d.w.). Isobe et al (2007) carried out an extensive monitoring survey in South and Southeast Asia coasts, reporting NP concentrations in mussels from 18 g/kg d.w. in Malaysia to 1347 g/kg d.w. in Tokyo Bay. The rapid population growth and drastic industrialization in South and Southeast Asia during the last decades, together with the no regulation of alkylphenol compounds in these countries, explain the significant NP concentrations observed especially in high industrialised regions.…”
Section: Alkylphenols Results In Mussels and Clamsmentioning
confidence: 99%